Ginkgo biloba attenuated detrimental inflammatory and oxidative events due to Trypanosoma brucei rhodesiense in mice treated with melarsoprol. - Janet Khatenje Wendo; James Mucunu Mbaria; James Nyabuga Nyariki; Alfred Orina Isaac (Public Library of Science (PLoS), 2024)
Background The severe late stage Human African Trypanosomiasis (HAT) caused by Trypanosoma brucei rhodesiense (T.b.r) is characterized by damage to the blood brain barrier, severe brain inflammation, oxidative stress and organ damage. Melarsoprol (MelB) is currently the only treatment available for this disease. MelB use is limited by its lethal neurotoxicity due to post-treatment reactive encephalopathy. This study sought to assess the potential of Ginkgo biloba (GB), a potent anti-inflammatory and antioxidant, to protect the integrity of the blood brain barrier and ameliorate detrimental inflammatory and oxidative events due to T.b.r in mice treated with MelB. Methodology Group one constituted the control; group two was infected with T.b.r; group three was infected with T.b.r and treated with 2.2 mg/kg melarsoprol for 10 days; group four was infected with T.b.r and administered with GB 80 mg/kg for 30 days; group five was given GB 80mg/kg for two weeks before infection with T.b.r, and continued thereafter and group six was infected with T.b.r, administered with GB and treated with MelB. Results Co-administration of MelB and GB improved the survival rate of infected mice. When administered separately, MelB and GB protected the integrity of the blood brain barrier and improved neurological function in infected mice. Furthermore, the administration of MelB and GB prevented T.b.r-induced microcytic hypochromic anaemia and thrombocytopenia, as well as T.b.r-driven downregulation of total WBCs. Glutathione analysis showed that co-administration of MelB and GB prevented T.b.r-induced oxidative stress in the brain, spleen, heart and lungs. Notably, GB averted peroxidation and oxidant damage by ameliorating T.b.r and MelB-driven elevation of malondialdehyde (MDA) in the brain, kidney and liver. In fact, the co-administered group for the liver, registered the lowest MDA levels for infected mice. T.b.r-driven elevation of serum TNF-α, IFN-γ, uric acid and urea was abrogated by MelB and GB. Co-administration of MelB and GB was most effective in stabilizing TNFα levels. GB attenuated T.b.r and MelB-driven up-regulation of nitrite. Conclusion Utilization of GB as an adjuvant therapy may ameliorate detrimental effects caused by T.b.r infection and MelB toxicity during late stage HAT.